Medical, pharmacological and neurosurgical perspectives on trigeminal neuralgia. (3rd August 2018) - Dexter, Mark; Aggarwal, Arun
Abstract: Trigeminal neuralgia (TN) is a chronic pain condition that affects the trigeminal cranial nerve. The typical or 'classic' form of the disorder (called 'Type 1' or TN1) causes sudden electric‐shock‐like pain that lasts anywhere from a few seconds to a few minutes. These attacks can last up to 2 h. There can be months or years between attacks, but in some patients, pain is not well controlled and can lead to a chronic pain syndrome. The 'atypical' form of the disorder (called 'Type 2' or TN2), is characterised by constant rather than intermittent aching, burning, stabbing pain.